DNA-Aptamer Targeting Vimentin for Tumor Therapy In Vivo - Zamay, Tatyana N. (Mary Ann Liebert, Inc., 2014)
In recent years, new prospects for the use of nucleic acids as anticancer drugs have been discovered. Aptamers for intracellular targets can regulate cellular functions and cause cell death or proliferation. However, intracellular aptamers have limited use for therapeutic applications due to their low bioavailability. In this work, we selected DNA aptamers to cell organelles and nucleus of cancer cells, and showed that an aptamer NAS-24 binds to vimentin and causes apoptosis of mouse ascites adenocarcinoma cells in vitro and in vivo. To deliver the aptamer NAS-24 inside cells, natural polysaccharide arabinogalactan was used as a carrier reagent. The mixture of arabinogalactan and NAS-24 was injected intraperitonealy for 5 days into mice with adenocarcinoma and inhibited adenocarcinoma growth more effectively than free arabinogalactan or the aptamer alone. The use of aptamers to intracellular targets together with arabinogalactan becomes a promising approach for anticancer therapy.